Data Mining Analysis Research on Intelligent Application of Cloud Accounting——Taking Cloud Accounting and Financial Sharing Center as an Example. Issue 4 (April 2021) - He, Qinwei
Abstract: This paper takes the cloud accounting and financial sharing center as the research object. It firstly expounds and analyzes the current status of cloud accounting and financial sharing, its operation management, and data mining intelligence, and provides necessary theoretical support for subsequent optimization. Secondly, through field research, interviews and collection of relevant materials, the current status of cloud accounting and financial sharing center operation management is described and the problems are analyzed. During the description of the current status, problems that can be optimized based on the intelligent perspective of data mining are found. Including performance management, risk management and process management modules. It enriches the method and technical system of cloud accounting and financial sharing centre's operation management optimization, contributes to the intelligence and automation of cloud accounting and financial sharing centre's operation management, effectively reduces the cost of operation management of cloud accounting and financial sharing center, and improves the operational management quality.